PENGARUH PERILAKU ORGANISASI DAN E-LELANG KEGIATAN KONSTRUKSI & PENGADAAN TERHADAP KINERJA PEGAWAI CV. PESONA ALAM KEDIRI - Kristina Kristina (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Organizational behavior on employee focus to how to think, feel and behavior of individuals, groups and organizations on the personality and attitude or behavior is influenced by motivation, abilities (ability) and perceptions of personality, values (values), perceptions, emotions, attitudes and stress. Employee performance is determined by leadership in the organization. The behavior of employees who either positive influence on their performance so needed motivation to encourage employees to improve job satisfaction with organizational culture that has an influence on organizational behavior so that it affects job satisfaction which can improve the performance of its employees . The purpose of this study is to find out how much influence Organizational Behavior upon servant performance, to find out how much influence E-Auction Event Construction and Procurement upon servant performance, to find out how much influence Organizational Behavior and E-Auction Construction and Acquisition Activity upon servant performance. The method used is quantitative, from 28 respondents CV employees. PESONA ALAM district Kediri who worked for at least 1 year by giving answers to the questionnaire . The results of this study are the Effects of Organizational and E- Auction on employee Performance showed significant 0.000 (b) which means that the variable behavior of Organitation and E-Auctions are significantly may affect the variable employees performance. Influence of Organizational Behavior against Employees performance show influence positively and significantly to the performance of these employees were necessary to achieve the effectiveness and success of an organization. Effect of E-Auction of the performance of employees affect positive and significant on the performance of employees, Organizational Behavior dominant influence to variable Y is compared with the variable Employee Performance X2 is E - Auction. Employees who have high levels of job satisfaction are more likely to behave extra roles. The results of this study are expected to be useful in developing the following research on organizational behavior